Vascular restenosis reduction with platelet membrane coated nanoparticle directed M2 macrophage polarization - Li, Fengshi; Rong, Zhihua; Zhang, Rui; Niu, Shuai; Di, Xiao; Ni, Leng; Liu, Changwei (iScience, 2022)
Vascular restenosis is the main factor affecting the prognosis of angioplasty in cardiovascular diseases, and inflammation is a central link in the progression of restenosis. Previous research that applies interleukin 10 (IL10) nanoparticles can effectively regulate local inflammation, but their targeted delivery efficacy remains to be improved. In this study, IL10 nanoparticles were successfully prepared and then coated by a preactive platelet membrane. The ability to target and regulate macrophage polarization has been demonstrated, thereby regulating smooth muscle cell and endothelial cell functions. In vivo experiments were carried out in a carotid artery injury model and verified the above functions and the effect on inhibiting vascular restenosis. Immune regulation-based platelet membrane coated nanoparticle loaded with IL10 proved to be an excellent candidate for targeting vascular injury and holds promise as an innovative drug delivery system for suppressing vascular restenosis. [Display omitted] •Targeted immune regulation can reduce restenosis after vascular injury•IL10-PNP can target and regulate M2 macrophages polarization in vivo•Vascular restenosis reduction mediated by IL10-PNP requires less cell membrane quantity Drug delivery system; Nanoparticles; Immune response